Efflux-mediated resistance to a benzothiadiazol derivative effective against Burkholderia cenocepacia - Scoffone, Viola Camilla; Ryabova, Olga; Makarov, Vadim; Iadarola, Paolo; Fumagalli, Marco; Fondi, Marco; Fani, Renato; De Rossi, Edda; Riccardi, Giovanna; Buroni, Silvia (Frontiers in Microbiology, 2015)
Burkholderia cenocepacia is a major concern for people suffering from Cystic Fibrosis as it contributes to serious respiratory tract infections. The lack of drugs effective against this opportunistic pathogen, along with the high level of resistance to multiple antibiotics, render the treatment of these infections particularly difficult. Here a new compound, belonging to the 2,1,3-benzothiadiazol-5-yl family (10126109), with a bactericidal effect and a MIC of 8 µg/ml against B. cenocepacia, is described. The compound is not cytotoxic and effective against B. cenocepacia clinical isolates and members of all the known Burkholderia cepacia complex species. Spontaneous mutants resistant to 10126109 were isolated and mutations in the MerR transcriptional regulator BCAM1948 were identified. In this way, a mechanism of resistance to this new molecule was described, which relies on the overexpression of the RND-9 efflux pump. Indeed, rnd-9 overexpression was confirmed by qRT-PCR, and RND-9 was identified in the membrane fractions of the mutant strains. Moreover, the increase in the MIC values of different drugs in the mutant strains, together with complementation experiments, suggested the involvement of RND-9 in the efflux of 10126109, thus indicating again the central role of efflux transporters in B. cenocepacia drug resistance.